Lower Urinary Tract Symptoms (LUTS) among women attending gynaecology clinic and its effect on their social life - Nusee, Zalina; Rerah, Ruqaiyah B.; Htyke, Myat Phyu; Abdulwahab, Dalia F; Ismail, Hamizah; Ramli, Roszaman; Awang, Mokhtar; Ismail, Rozihan (The Faculty of Medicine, International Islamic University Malaysia, 2015)

(untitled)
Introduction: Lower Urinary Tract Symptoms (LUTS) is a worldwide problem that is highly prevalent and varies by age, geography and culture. It influences the quality of life with a myriad of social implications. Objective: To estimate the prevalence of LUTS among patients attending the gynaecology clinic. We also assessed its severity and associated risk factors. Methodology: This is a cross sectional study where participants were given 3 sets of self-filled questionnaire; UDI-6, IIQ-7 and OAB v8. IMJM Vol. 14, Supplement Issue, Dec 2015 5 | M e dical Research Symposium 2015 Results: The prevalence of LUTs was 62%. The commonest symptoms were frequency (43%) and stress incontinence (49%). It was significantly associated with BMI, past obstetric history, menopausal status and previous pelvic surgery. Storage symptoms including stress urinary incontinence (SUI) and overactive bladder (OAB); and voiding dysfunction also shows significant associations. For SUI, the subject’s race, hormonal therapy status and smoking history were not significant. For OAB, other than race, HRT and smoking, BMI was also not significant. For voiding dysfunction, other than HRT and smoking, parity and menopausal status were also not significant. Conclusion: This study shows that LUTS is highly prevalent in our population. However, further longitudinal studies are need to better understand the severity and potential impact on quality of life.